2019
DOI: 10.2147/ijwh.s197604
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ovarian cancer in the world: epidemiology and risk factors</p>

Abstract: Aim: Ovarian cancer is one of the most common gynecologic cancers that has the highest mortality rate. Considering the fact that knowledge on the incidence, mortality of ovarian cancer, as well as its risk factors is necessary for planning and preventing complications, this study was conducted with the aim of examining the epidemiology and risk factors of ovarian cancer in the world. Materials and methods: In order to access the articles, Medline, Web of Science Core Collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
519
1
32

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 683 publications
(562 citation statements)
references
References 147 publications
10
519
1
32
Order By: Relevance
“…Ovarian cancer (OC) is one of the most common gynecological cancers that have the worst prognosis and the highest mortality rate in women worldwide (Momenimovahed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer (OC) is one of the most common gynecological cancers that have the worst prognosis and the highest mortality rate in women worldwide (Momenimovahed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer, the third‐ranked gynecologic cancer, has been reported to have a high mortality rate and a poor prognosis . Various factors such as metabolic disorders in women with polycystic ovary syndrome may be related to gynecologic cancers .…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the lower prevalence of ovarian cancer compared to breast cancer, its mortality rate is three times higher than breast cancer. Moreover, predictions have shown that this mortality rate will increase significantly by the year 2040 . Based on the classification of the World Health Organization, epithelial ovarian carcinomas (EOCs) can be divided into different subgroups related to cell types: serous carcinomas (SCs), mucinous carcinomas, endometrioid carcinomas (ECs), clear‐cell carcinomas, transitional‐cell Brenner tumors, and mixed and undifferentiated type .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations